Validation of a New Instrument to Measure Breastfeeding Understanding Among Adults. (29th May 2020) - McKinley, Erin
Abstract: Objectives: The current literature on breastfeeding understanding scales is limited and has yet to contain a scale that does not incorporate items related to breastfeeding attitude. Asking questions related to attitude may skew how an individual answers items related to knowledge. A positive or negative viewpoint of breastfeeding does not adequately reflect understanding. Knowledge and understanding should be evaluated against an individual's level of health literacy, as that may have a strong impact on choices related to infant feeding. The aims of this study were to create, test, and validate a new scale to measure breastfeeding understanding among adults and evaluate the relationship between that and level of health literacy. Methods: A 68-item, online-platform based survey to evaluate breastfeeding knowledge, understanding, and demographics was created for this study. The 50-item scale to be validated assessed participants' general understanding and knowledge about breastfeeding and human lactation. Health literacy was assessed using the Single-Item Literacy Screener (SILS). Results: Seven-hundred and twenty-two adults, 18 years of age or older, completed the web-based survey instrument. Construct validity was examined using an exploratory factor analysis utilizing principle axis factoring with promax rotation. This confirmed a valid (α = .953) five factor scale for knowledge and understanding of breastfeeding – The Adult Breastfeeding Understanding Scale (A-BFUS). Total A-BFUS score was significantly correlated to health literacy level ( P  < .001). Participants with low health literacy had significantly lower total A-BFUS scores ( P  < .001) than those with adequate or high health literacy (173.02 ± 20.08 vs. 188.07 ± 27.16). Conclusions: A measurement scale for breastfeeding knowledge that is valid for use among adults of any gender identification is vital to the creation and evaluation of breastfeeding education programs aimed at increasing general understanding. Incorporating educational efforts to improve health literacy of individuals may strengthen program success and increase positive choices related to multiple areas of health. Funding Sources: This material is based upon work that is supported by the National Institute of Food and Agriculture, U.S. Department of Agriculture, Hatch project under XXXXXXXX.